Characterization of polysulfides in Saccharomyces cerevisiae cells and finished wine from a cysteine-supplemented model grape medium. (February 2023) - Huang, Chien-Wei; Deed, Rebecca C.; Parish-Virtue, Katie; Pilkington, Lisa I.; Walker, Michelle E.; Jiranek, Vladimir; Fedrizzi, Bruno
Abstract: Polysulfide degradation in wine can result in hydrogen sulfide (H2 S) release, imparting a rotten-egg smell that is detrimental to wine quality. Although the presence of wine polysulfides has been demonstrated, their biogenesis remains unclear. This study investigated the role of Saccharomyces cerevisiae in polysulfide formation during fermentation, with and without 5 mM cysteine supplementation as an H2 S source. Using an established liquid chromatography-tandem mass spectrometry method, monobromobimane derivatives of hydropolysulfides, including CysSSSH, CysSSSSH and GSSSSH, and two oxidized polysulfides, GSSG and GSSSSG, were detected in yeast cells at the end of fermentation in a grape juice-like medium. Polysulfide production by four S. cerevisiae single deletion mutants (BY4743 Δ cys3, Δ cys4, Δ met17 and Δ tum1 ) showed no significant differences compared to BY4743, suggesting that uncharacterized pathways maintain cellular polysulfide homeostasis. Five mM cysteine addition increased the formation of shorter sulfur chain species, including GSS-bimane and GSSG, but did not elevate levels of longer sulfur chain species. Additionally, polysulfides with even numbers of sulfur atoms tended to predominate in cellular lysates. Oxidized polysulfides and longer chain hydropolysulfides were not detected in finished wines. This evidence suggests that these polysulfides are unstable in wine-like environments or not transported extracellularly. Collectively, our data illustrate the complexity of yeast polysulfide metabolism under fermentation conditions. Highlights: Hydro- and oxidized polysulfides were identified inside yeast cells post-fermentation. Polysulfide production within sulfur pathway mutants and wild type was comparable. Supplementation with high cysteine increased short chain polysulfide formation. Polysulfides with even numbered sulfur atoms dominated in cells and finished wine.